Transparent lithium aluminum silicate glass ceramic

JP2025015488APending Publication Date: 2025-01-30SCHOTT AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024114550
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-19
Filing Date
2024-07-18
Publication Date
2025-01-30

Smart Images

  • Figure 2025015488000001
    Figure 2025015488000001
  • Figure 2025015488000002
    Figure 2025015488000002
  • Figure 2025015488000003
    Figure 2025015488000003
Patent Text Reader

Abstract

To provide a transparent lithium aluminum silicate glass ceramic suitable for use as a cooktop for cooking devices.SOLUTION: A glass ceramic has a coefficient of thermal expansion of -0.8 to 1.5 ppm / K in the range of 20°C and 700°C, a light transmittance τvis of more than 75% at a thickness of 4 mm, and a chroma value C* of less than 10 at a thickness of 4 mm. The glass ceramic comprises, expressed in weight percent on an oxide basis, SiO2: 62-68, Al2O3: 19-24, Li2O: 2.4-3.1, BaO:>2.5, ZnO:>2.5, ZrO2:>1.5, Na2O: 0-1, and K2O: 0-1.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to transparent lithium aluminium silicate glass-ceramics, particularly suitable for use as cooktops in cooking appliances, and their uses.

[0002] 2. Background of the Invention Glass-ceramics, especially transparent glass-ceramics, have been known for a long time. One variant of such glass-ceramics also known in the prior art is the lithium aluminum silicate (LAS) glass-ceramics, which contain as the main crystalline phase either a high quartz solid solution (HQMK), especially for transparent materials, or a keatite solid solution (KMK), especially for translucent or opaque materials. To produce such glass-ceramics, a starting glass, the so-called green glass, is first produced in a manner customary for glass production. This green glass is converted into a glass-ceramic by a heat treatment known as ceramization. The transparent glass-ceramics thus produced can be used in a wide range of applications. In particular, such glass-ceramics are used as cooktops. Furthermore, such glass-ceramics are used as sight glasses for stoves and ovens, worktops or safety glass.

[0003] An essential property of these materials used as cooktops is their very low coefficient of thermal expansion in the temperature range from room temperature to 700 °C. The low coefficient of thermal expansion results in high thermal shock resistance. The coefficient of thermal expansion is set by the combination of a crystalline phase with a negative coefficient of thermal expansion and an amorphous residual glass phase with a positive coefficient of thermal expansion. In conventional glass-ceramics, a proportion of lithium oxide of more than 3.6% by weight and up to 5.0% by weight is usually used for this purpose.

[0004] Due to the rising cost of lithium as a raw material, it is advantageous for economic reasons to minimize the proportion of lithium in glass-ceramics. However, lithium cannot simply be reduced at will, since it is one of the three main components of lithium aluminum silicate glass-ceramics. The proportion of Li2O directly affects the key properties of glass-ceramics, such as their viscosity during melting and hot forming, which is important for manufacturability, and their thermal expansion coefficient, which is important for use as cooktops.

[0005] The price of lithium is not a new issue. It has been rising steadily for the past 20 years. Despite this long-standing need, most commercially available glass-ceramics for cooktops contain more than about 3.8% Li2O by weight.

[0006] Glass-ceramics with a proportion of LiO of less than 3.5% by weight are known from WO 2012 / 010341, EP 3502069, US 2017050880, US 2020189965, US 2020140322, US 2021387899, WO 2021 / 224412. However, these glass-ceramics have various disadvantages, such as, for example, reduced thermal shock resistance and poor melting of green glasses.

[0007] A basic approach which allows the production of lithium aluminium silicate glass-ceramics which avoid the abovementioned disadvantages even with a low Li2O content has been described by the applicant, for example, in DE Utility Model No. 202022106826, where an approach which allows the production of transparent glass-ceramics with a low Li2O content is also described.

[0008] Here, transparent glass-ceramics have other special requirements in addition to the above-mentioned temperature stability. When transparent glass-ceramics are used as cooktops, they are usually provided with a colored underside coating so that heating elements and associated electronics arranged below the glass-ceramic are not visible from above the glass-ceramic. In this case, it is generally required that the color perception of such underside coating by the end user is not distorted by the glass-ceramic. When transparent glass-ceramics are used as viewing windows, similar requirements are imposed on the glass-ceramic, since in this case too, color distortion when viewed through the viewing window must be avoided.

[0009] Transparent glass-ceramics are understood in this context, as is customary, to be glass-ceramics that have low light scattering, the transmittance of which can be adjusted over a wide range using absorbing, i.e. coloring, components.

[0010] Problems to be Solved by the Invention The object of the present invention is to provide transparent lithium aluminum silicate glass-ceramics which have the good melting properties of green glasses and are cost-effective, but which do not result in restrictions on the properties of use. Furthermore, it is desirable for the glass-ceramics according to the invention to have as little distortion of color perception as possible due to the glass-ceramics.

[0011] Here, good melting properties include in particular a processing point of less than or equal to 1340° C., advantageously less than 1330° C., particularly preferably less than 1320° C. The processing point is defined as a temperature at which the green glass melts at 10 4 This is the temperature at which the glass has a viscosity of 1000 dPa·s. Hot forming of green glass is carried out around this temperature. The higher the temperature during hot forming, the more costly it is to dissipate the heat introduced by the glass into the forming machine. At temperatures above 1340°C, this can only be achieved by reducing the heat load by reducing the throughput of the glass volume. However, this is economically disadvantageous.

[0012] If the so-called upper devitrification temperature is exceeded during hot forming, undesirable spontaneous crystallization (also called "devitrification") can occur. In order to prevent this, it is advantageous for the upper devitrification temperature to be at least 10 K, preferably at least 15 K, particularly preferably at least 20 K, very particularly preferably at least 30 K lower than the processing point.

[0013] Glass-ceramics should in particular meet all requirements for use as cooktops with all types of heating elements, including in particular radiant, inductive and gas heating elements, which in particular require a sufficiently high thermal shock resistance as well as a high long-term thermal resistance.

[0014] Summary of the Invention The problem of the invention is solved by the subject matter of the independent claims. Preferred embodiments and developments can be found in the dependent claims.

[0015] The transparent lithium aluminum silicate glass ceramic according to the present invention has a thermal expansion coefficient of -0.8 to 1.5 ppm / K in the range of 20°C to 700°C, and a light transmittance τ vis exceeds 75%, and saturation at a thickness of 4 mm is C * is less than 10, wherein the glass-ceramics contain the following components in the indicated amounts, expressed in weight percent on an oxide basis: SiO262~68 Al2O319~24 Li2O 2.4~3.1 BaO >2.5 ZnO >2.5 ZrO2>1.5 Na2O 0~1 K2O 0~1.

[0016] Glass-ceramics with an appropriate thermal expansion coefficient combine high thermal shock resistance with high long-term thermal stability, making them suitable for use as cooktops with any type of heating element. The thermal expansion coefficient is at least -0.8 ppm / K, where "ppm" stands for "parts per million," i.e. 10 parts per million for a temperature change of 1 K. -6 This refers to the change in the relative magnitude of the thermal expansion coefficient. A shift in the thermal expansion coefficient values ​​towards a more negative direction is to be avoided. In the case of a negative expansion coefficient, i.e. contraction, tensile stresses arise on the surface of the glass-ceramics during heating. For values ​​below -0.8 ppm / K, these stresses can reduce the mechanical strength of the cooktop at typical operating temperatures of the cookware. A thermal expansion coefficient of more than 1.5 ppm / K is likewise to be avoided. A thermal expansion coefficient of more than 1.5 ppm / K does not ensure sufficient thermal shock resistance for the use of glass-ceramics in cookware with radiant heating elements.

[0017] In one development of the invention, the thermal expansion coefficient is at least -0.6 ppm / K, -0.4 ppm / K, -0.2 ppm / K, 0.0 ppm / K, 0.2 ppm / K, 0.4 ppm / K, 0.6 ppm / K or even 0.8 ppm / K. Furthermore, the thermal expansion coefficient is advantageously at most 1.4 ppm / K, 1.3 ppm / K, 1.2 ppm / K, 1.1 ppm / K, 1.0 ppm / K, 0.8 ppm / K or even at most only 0.6 ppm / K.

[0018] In a preferred embodiment of the invention, the glass-ceramics have a thermal expansion coefficient of -0.8 to 0.8 ppm / K, advantageously -0.5 to 0.5 ppm / K, particularly preferred -0.3 to 0.3 ppm / K. Such glass-ceramics are particularly suitable for cooktops of cooking appliances equipped with radiant or induction heating elements.

[0019] With regard to the optical properties given in terms of transmittance and saturation of the glass-ceramics according to the invention, "at a thickness of 4 mm" means that the corresponding properties are measured on a sample with a material thickness of 4 mm or are measured at another material thickness and converted to a material thickness of 4 mm. In the case of transmittance data, the conversion can be carried out using the Beer-Lambert law.

[0020] Light transmittance τ vis is measured in the wavelength range of 380-780 nm using standard illuminant D65 and a 2° observer in accordance with the specifications of DIN 5033. This value corresponds to the luminance Y in the CIExyY color space.

[0021] Saturation C * , L * a * b * It is determined from the color coordinates according to the following formula:

number

[0022] Colour coordinates a * and b * is determined in a known manner from the transmission spectrum of the glass-ceramics using standard illuminant D65 and a 2° observer.

[0023] Glass ceramics with a light transmission of more than 75% at a thickness of 4 mm are particularly suitable for use as fireplace viewing windows or cook panels. In fireplaces, this transmission allows a particularly good view of the fire. In cooking appliances, this transmission allows a particularly good view of relatively low-brightness light displays, such as LCD displays or OLED displays. The glass ceramics according to the invention here preferably have a light transmission τ of more than 80%, particularly preferably more than 83%, very particularly preferably more than 85%. vis has.

[0024] Saturation C *A D of less than 10 ensures that the color of light changes only slightly when passing through the glass-ceramic, which is particularly important when used as a viewing window for cooktops or fireplaces, for example.

[0025] The saturation of glass ceramics is particularly noticeable, for example, when the glass ceramics are provided with a white or generally light-colored underside coating when used as a cooktop. Glass ceramics for such applications are often 4 mm thick. The light reflected by the back coating therefore has to travel an 8 mm optical path, in which case the color shift due to the inherent color of the glass ceramics has a greater effect than if the optical path were shorter. A correspondingly low saturation is therefore particularly advantageous for cooktops or fireplace viewing windows with a white coating on the back. Preferably, the glass ceramics according to the invention here have a saturation C of less than 8, particularly preferably less than 6 and very particularly preferably less than 5. * has.

[0026] The glass ceramic according to the invention comprises the following components in % by weight: SiO262~68, Al2O319-24, and Li2O 2.4~3.1.

[0027] The components SiO2 and Al2O3 form the main crystalline phase together with Li2O in glass-ceramics. At the same time, they greatly influence the glass-forming properties and the viscosity of the green glass.

[0028] The SiO2 content of the glass ceramics according to the invention should be at most 68% by weight, since this component significantly increases the viscosity of the glass, in particular the processing point. In order to obtain good melting of the glass and low forming temperatures, a higher SiO2 content is uneconomical. If the proportion of SiO2 is too high, exceeding 68% by weight, keatite may form during ceramization. This leads to a significant increase in the coefficient of thermal expansion and a deterioration of the optical properties of the material, in particular in the form of haze. Here, the minimum content of SiO2 should be 62% by weight, since this is favorable for the required properties, for example chemical and heat resistance.

[0029] Advantageously, the glass ceramic comprises at least 63% or even 64% by weight of SiO2. The more SiO2 contained in the glass ceramic, the better its heat and chemical resistance. Furthermore, the glass ceramic advantageously comprises only up to 67% by weight, up to 66% by weight or even up to 65% by weight of SiO2. The less SiO2 contained in the glass ceramic, the better the meltability and processability of the green glass in hot forming.

[0030] The Al2O3 content of the glass-ceramics according to the invention is in the range of 19-24% by weight. At higher proportions of Al2O3, devitrification and undesired mullite formation become problematic. It should therefore not exceed 24% by weight. An amount of Al2O3 less than 19% by weight is detrimental to the formation of high-quartz solid solutions and promotes the formation of undesirable crystalline phases. It has also been found that a low Al2O3 content has a detrimental effect on the saturation of the glass-ceramics.

[0031] Advantageously, the glass ceramic contains at least 20% by weight of Al2O3, preferably at least 21% by weight of Al2O3. The more Al2O3 contained in the glass ceramic, the better its heat resistance. Furthermore, the glass ceramic advantageously contains up to 23% by weight of Al2O3, particularly preferably up to 22% by weight of Al2O3. The less Al2O3 contained in the glass ceramic, the better the meltability and processability of the green glass in hot forming.

[0032] The Li2O content of the glass ceramics according to the invention is in the range of 2.4-3.1% by weight. It has been found that with a Li2O content in this range, in combination with the remaining components in the limits mentioned, it is possible to obtain glass ceramics with high thermal shock resistance and good melting properties. Since Li2O has a significant effect on the thermal expansion coefficient of the glass ceramics, Li2O is selected in the above mentioned limits in combination with the remaining components of the glass ceramics according to the invention so as to achieve the thermal shock resistance required for the invention. In addition, a proportion of Li2O exceeding 2.4% by weight reduces the electrical resistance of the glass melt, reduces the viscosity and thus the processing point, thus favorably affecting the manufacturability of the glass ceramics. The reduced viscosity of the glass melt also makes it possible to improve the efficiency of the fining process. The improved fining process reduces production waste due to bubble formation in the green glass. Li2O also reduces the tendency of the green glass to devitrify.

[0033] In a preferred embodiment, the glass-ceramics contain at least 2.5%, 2.6%, or even 2.7% by weight of LiO.

[0034] The lithium sources used for the production of glass-ceramics are usually either natural mineral sources such as spodumene or petalite, or synthetically produced Li2CO3.

[0035] In a preferred embodiment, the glass ceramic comprises a high-quartz solid solution as the main crystalline phase. By "main crystalline phase" it is meant that the glass ceramic comprises, by volume percentage, more high-quartz solid solution than keatite solid solution and other crystalline phases. In one development of this embodiment, the glass ceramic comprises <10 vol. %, preferably <5 vol. %, particularly preferably <3 vol. % keatite solid solution, where these volume percentage data are relative to the volume of the glass ceramic. The volume percentage is determined by Rietveld refinement from the X-ray diffraction spectrum.

[0036] Keatite solid solutions generally have a higher thermal expansion coefficient than high-quartz solid solutions. Therefore, in order to reduce the thermal expansion coefficient of the glass-ceramics, it is particularly preferable to increase the proportion of high-quartz solid solutions and at the same time reduce the proportion of keatite solid solutions. A low thermal expansion coefficient also improves the thermal shock resistance of the glass-ceramics. At the same time, an excessively high proportion of keatite adversely affects the optical properties of the glass-ceramics, since keatite solid solutions usually cause strong scattering of light due to their large crystallite size. For this reason too, the content of keatite in the crystalline phase should be kept as low as possible.

[0037] In addition to the aforementioned amounts of SiO2, Al2O3 and Li2O, the glass ceramics according to the invention contain more than 2.5% by weight of ZnO, preferably more than 2.6% by weight, more than 2.7% by weight, more than 2.8% by weight or more than 2.9% by weight of ZnO, particularly preferably more than 3.0% by weight and very particularly preferably more than 3.2% by weight of ZnO. The contribution of Li2O to the reduction of the thermal expansion coefficient of the glass ceramics has already been explained above. Thus, if the Li2O content is reduced below the proportions usually used in the prior art for transparent glass ceramics, the reduction of the thermal expansion coefficient of the high quartz solid solution in the glass ceramics is reduced, so that the expansion coefficient required for use as a cooktop may not be achieved. However, since ZnO, like Li2O, also contributes to the reduction of the thermal expansion coefficient, the effect of the reduction of the Li2O content can be at least partially counteracted by increasing the ZnO content to values ​​above 2.5% by weight.

[0038] ZnO also lowers the processing point and the upper devitrification temperature of the glass-ceramics. However, ZnO can lead to the formation of undesirable gahnite crystals, especially in combination with a large amount of Al2O3. For this reason, its content in the glass-ceramics is advantageously limited to 6.0% by weight. Furthermore, it has been empirically found that glass-ceramics containing very large amounts of ZnO tend to form undesirable crystals on the glass-ceramic surface. Therefore, the amount of ZnO is advantageously limited to an amount of 5.6%, 5.3%, 5.0%, 4.6%, 4.3%, 4.0% or even 3.7% by weight or less.

[0039] Moreover, an excessive increase in ZnO content will increase the difference in refractive index between the crystalline phase and the residual glass phase in the glass-ceramics, causing the corresponding glass-ceramics to scatter the incident light more strongly. As a result, an increase in the ZnO content may have a negative effect on the transmittance and saturation of the glass-ceramics.

[0040] To counter this effect, the glass ceramics according to the invention also contain more than 2.5% by weight of BaO. As the proportion of BaO increases, the tendency of the glass ceramic to scatter the incident light decreases, since the addition of BaO allows the refractive index of the residual glass phase of the same crystallite size to be equal to the refractive index of the crystalline phase of the glass ceramic. This effect is seen when the proportions of Li2O and ZnO are within the limits mentioned above, especially when the contents of SrO and CaO in the glass ceramic are low at the same time.

[0041] BaO, like Li2O, further reduces the viscosity of the glass melt and thus the processing point. In order to improve the meltability of the green glass, it is advantageous for the glass ceramic to contain more than 2.6 wt.%, more than 2.7 wt.%, more than 2.8 wt.%, more than 2.9 wt.%, or even more than 3.0 wt.% BaO in combination with the above-mentioned amount of Li2O. In the glass ceramic, BaO also contributes significantly to improving the devitrification behavior during hot forming of the green glass. Here, the content of BaO is preferably limited to less than 4.0 wt.%, less than 3.9 wt.%, less than 3.8 wt.%, less than 3.7 wt.%, less than 3.6 wt.%, less than 3.5 wt.%, less than 3.4 wt.%, less than 3.3 wt.%, or even less than 3.2 wt.%.

[0042] Furthermore, the glass-ceramics according to the invention contain more than 1.5% by weight of ZrO2, which acts in particular as a nucleating agent in the glass-ceramics and can itself interact with other components of the glass-ceramics, such as SnO2 and TiO2, whereby a content of ZrO2 of more than 1.5% by weight is advantageous for improved nucleation.

[0043] Here, in one development of the invention, the amount of ZrO2 can be limited to a value of 3.0% by weight, since ZrO2 deteriorates the melting behavior of the batch. Furthermore, ZrO2 can cause devitrification during hot forming. In this case, this can lead to the formation of undesirable Zr-containing crystalline phases, such as baddeleyite. Advantageously, the glass ceramics contain at least >1.6% by weight, particularly preferably >1.7% by weight, very particularly preferably >1.8% by weight of ZrO2. Furthermore, the glass ceramics advantageously contain 2.9% by weight, 2.8% by weight, 2.6% by weight, 2.5% by weight, 2.4% by weight, 2.3% by weight, 2.2% by weight, 2.1% by weight, or even only 2.0% by weight or less of ZrO2. With these amounts, a particularly good compromise can be achieved between a positive contribution to nucleation and a still tolerable deterioration of meltability and hot forming. Here, it is possible to further enable faster ceramization of the green glass by optimizing the ZrO2 content, especially taking into account the TiO2 content in the glass-ceramics described below.More rapid ceramization upon sufficient preceding nucleation leads to smaller crystallite sizes in the glass-ceramics and less light scattering.

[0044] A Na2O content of 0-1% by weight in the glass-ceramics according to the invention further improves the meltability and the devitrification behavior during glass forming. Furthermore, Na2O can increase the electrical conductivity of the melt. This facilitates the coupling of energy by the electric heater in the melting bath. However, the content is limited, since it is not incorporated into the crystalline phase but remains substantially in the residual glass phase of the glass-ceramics. An excessively high content impairs the crystallization behavior during the conversion of the crystallizable starting glass into the glass-ceramics, here at the expense of a particularly high ceramization rate. This results in a larger crystallite size at a higher ceramization rate of the glass-ceramics, which has an unfavorable effect on the scattering behavior of the glass-ceramics. Furthermore, a high content has an unfavorable effect on the long-term durability / heat resistance of the glass-ceramics. For this reason, the glass-ceramics advantageously contain >0.1-1% by weight, or 0.2-0.8% by weight, or even 0.3-0.6% by weight of Na2O.

[0045] 0-1% by weight of K2O improves the meltability and the devitrification behavior during glass forming in the glass ceramics according to the invention. K2O can also further increase the electrical conductivity of the melt. This facilitates the coupling of energy by the electric heater in the melting bath. However, the content is limited, since it is not incorporated into the crystalline phase but remains substantially in the residual glass phase of the glass ceramic. If the content is too high, the crystallization behavior during the conversion of the crystallizable starting glass into the glass ceramic is impaired, here at the expense of a particularly high ceramization rate. Similar to the explanation above for Na2O, in this case too, an excessively high ceramization rate and thus a large crystallite size in the glass ceramic adversely affects the scattering behavior of the glass ceramic. Furthermore, a high content has an unfavorable effect on the long-term durability / heat resistance of the glass ceramic.

[0046] These properties are further improved if K2O is included in the glass-ceramics in an amount of 0.8 wt%, 0.6 wt%, 0.5 wt%, 0.4 wt%, or even 0.3 wt% or less. In a particular embodiment, it may be further provided that the glass-ceramics are free of K2O, except as unavoidable impurities.

[0047] In one development of the invention, it is further provided that the glass ceramics do not contain Cr2O3, V2O5, MnO2 and MoO3, except for unavoidable impurities. V2O5 and MoO3 are usually used as the main coloring agents for coloring volumetrically colored glass ceramics, while Cr2O3 and MnO2 are often used for auxiliary coloring. Since the above-mentioned coloring agents, especially V2O5, generally color the glass ceramics very strongly even in small amounts, it is desirable to keep the content of the above-mentioned components in the glass ceramics according to the invention as low as possible in order to guarantee the inventive transmittance and saturation of the glass ceramics. Here, these components are present, inter alia, as impurities in the raw materials of the batch or as components in cullet that is added to the batch to improve the melting properties. Here, "unavoidable impurities" is understood to mean a content of the respective component in the composition of less than 20 ppm, in particular less than 10 ppm, in particular less than 5 ppm. Furthermore, the glass ceramics preferably also do not contain Ce, Ni, Cu, Co, W and / or S or their oxides, except for unavoidable impurities.

[0048] In a preferred development of the invention, the glass ceramic comprises less than 3.0% by weight of TiO2. TiO2, together with ZrO2, contributes significantly to the nucleation. The amount of TiO2 is limited to a value of 3.0% by weight or less. A higher amount of TiO2 may cause devitrification during hot forming. This may further lead to an undesirable increase in the refractive index of the residual glass phase. Advantageously, the glass ceramic comprises at least 1%, 1.5%, 2.0%, >2.1% by weight of TiO2. At the same time, the glass ceramic advantageously comprises not more than 2.7%, 2.5% or even only not more than 2.4% by weight of TiO2. A high proportion of TiO2 leads to a faster nucleation process. This allows the ceramization time of the glass ceramic to be reduced. A low proportion leads to a stabilization of the ceramization process and prevents unintended devitrification during hot forming of the green glass. In summary, the upper limit of the TiO2 content is set in order to keep the coloring effect of TiO2 on the optical properties of the glass-ceramics as low as possible. At the same time, however, it is not desirable to select the TiO2 content too low, so that sufficient nucleation and short ceramization times are still guaranteed. In this case, by using the above-mentioned amount of ZrO2, the proportion of TiO2 as a further nucleating agent can be reduced, and thus a glass-ceramic with reduced saturation can be produced.

[0049] In one development of the invention, the glass ceramics contain less than 0.05% by weight, preferably less than 0.04% by weight, particularly preferably less than 0.03% by weight, very particularly preferably less than 0.02% by weight of Fe2O3. Like V2O5, Cr2O3, MnO2 and MoO3, Fe2O3 also has a coloring effect in glass ceramics. For this reason, it is advantageous for transparent glass ceramics to limit the content of Fe2O3 to the values ​​mentioned above. For example, glass ceramics containing Fe2O3 as a coloring agent often have a yellowish tinge. This can occur, for example, with glass ceramics that simultaneously contain TiO2 and Fe2O3 that is mixed in by impurities in the raw materials. If such glass ceramics are provided with a white underside coating, this underside coating has a clearly perceptible yellowish tinge.

[0050] Furthermore, Fe2O3 affects the transmittance not only in the visible range, but also in the near infrared range up to wavelengths of approximately 3 μm. Thus, Fe2O3 not only affects the realization of certain colors and the displayability of color displays. Absorption in the near infrared range determines how much heat energy the glass melt can absorb in the bath. This determines how much of the heat output from the radiant heating elements can pass through the glass ceramic. It also determines whether and which infrared sensors can be used in the stove. Such sensors can be designed, for example, as optical touch sensors or infrared receivers for wireless data transmission.

[0051] It should be noted here that within the scope of this disclosure, the components of the glasses are presented in the form that is usually obtained by analysis, where each component is usually presented in its stable, usually highest oxidation state, but it is pointed out that this does not necessarily correspond to the form in which the component actually exists.

[0052] For example, iron in oxide glasses exists in both divalent and trivalent forms, i.e., Fe 2+ or as FeO or as Fe 3+or Fe2O3. Thus, the data on the contents of the corresponding components in the scope of the present disclosure relate to the usual data of the analysis, but it is understood that each component may also be present in a form that deviates from the "ideal" oxidation state usually indicated.

[0053] In one development of the invention, the glass ceramics contain less than 1.2% by weight, preferably less than 1.0% by weight, particularly preferably less than 0.8% by weight, less than 0.7% by weight, less than 0.6% by weight, very particularly preferably less than 0.5% by weight of MgO, where MgO has a positive effect on the meltability and the devitrification behavior of the glass ceramics, but in excess it leads to an increase in the saturation of the glass ceramics and an increase in the thermal expansion coefficient of the high-quartz solid solution phase. It has therefore been found to be advantageous for colorless and transparent glass ceramics to limit the MgO content to the limits mentioned above.

[0054] According to a further development of the invention, it is further provided that the transparent lithium aluminum silicate glass ceramics contain less than 1.2% by weight, preferably less than 1.0% by weight, particularly preferably less than 0.8% by weight, very particularly preferably less than 0.5% by weight of CaO. In this case, CaO has an advantageous effect on the devitrification behavior of the glass ceramics. However, it has been found to be advantageous for colorless and transparent glass ceramics to limit the CaO content to the abovementioned values, since CaO contributes to an increase in the crystallite size in the glass ceramics. An increase in the crystallite size is accompanied by an increase in scattering and therefore a decrease in the optical properties of the glass ceramics.

[0055] In one development of the invention, the glass ceramics contain less than 0.2% by weight of SnO2, preferably less than 0.15% by weight, particularly preferably less than 0.1% by weight of SnO2. SnO2 assists in the fining of green glass. Glass ceramics containing the above-mentioned amounts of SnO2 are therefore characterized by a particularly low number of defects due to trapped gas bubbles. In this case, SnO2, in combination with other components of the glass ceramics according to the invention, further has a positive effect on nucleation. However, amounts of less than 0.2% by weight of SnO2 should not be exceeded, since it can adversely affect the optical properties of the glass ceramics, in particular causing an increase in the saturation of the glass ceramics. Higher contents of SnO2 also lead to undesirable crystallization of Sn-containing crystalline phases, such as cassiterite, on the contact material (e.g. Pt / Rh) during molding, which further deteriorates the optical properties of the glass ceramics.

[0056] Here, in order to support the fining of the green glass, in addition to the above-mentioned SnO2 content, a proportion of up to 2% by weight of As2O3 and / or Sb2O3 may be present. Since, as already explained, in addition to its positive effect on the fining of the green glass, SnO2 can have a negative effect on the optical properties of the glass-ceramics, it has proven advantageous to reduce the SnO2 content as much as possible. This is especially because SnO2 can form additional absorption bands for the incident light together with TiO2, resulting in a red shift of the transmitted light. Furthermore, SnO2 can also be used as a counterbalance to the Fe in Fe2O3. 2+ This may contribute to an increase in the proportion of TiO2, resulting in increased coloration when used in combination with TiO2.

[0057] As2O3 and Sb2O3 have substantially the same effect and therefore may be present in the glass-ceramics either alone or in combination. In either case, the amount should preferably not exceed 2% by weight each. The expression "As2O3 and / or Sb2O3" in this context means that both components may be present either alone or in combination in the corresponding amounts.

[0058] Thus, according to a further development of the invention, it is provided that the glass ceramics are free of SnO2, except for unavoidable impurities, and contain 0.5% to 1.5% by weight of As2O3 and / or Sb2O3. A fining process that is carried out completely free of SnO2 and thus avoids the above-mentioned influence of SnO2 on the optical properties of the glass ceramics is in this case particularly advantageous for the production of transparent, color-neutral glass ceramics. Unlike SnO2, As2O3 and Sb2O3 do not have as strong a reducing effect on Fe2O3 as SnO2 does, and therefore do not affect the color of the glass ceramics and do not lead to increased coloring when used in combination with TiO2.

[0059] In one development of the invention, it is further provided that the transparent lithium aluminum silicate glass-ceramics contain 0.01-0.07 wt. % Nd2O3, preferably 0.03-0.06 wt. % Nd2O3, which in this case contributes to offsetting the saturation of the glass-ceramics due to SnO2, especially when fining is carried out with SnO2. In this case, the addition of Nd2O3 is advantageous for the production of glass-ceramics with an almost neutral color tone, especially when the SnO2 content is more than 0.1 wt. %.

[0060] In glass-ceramics in which the Fe2O3 and TiO2 contents are within the abovementioned limits, the addition of Nd2O3 can further contribute to reducing or eliminating the yellow tint due to Fe2O3 and TiO2, with only a slight effect on the light transmittance. This effect is based on the narrow absorption bands of Nd2O3 in the visible light range at wavelengths of 513, 526, 575, 585 and 745 nm, which is particularly advantageous for the production of transparent, color-neutral glass-ceramics.

[0061] In summary, therefore, the fining of glass-ceramics can be carried out by the addition of SnO2 alone, by the combination of SnO2 with As2O3 and / or Sb2O3, or by pure fining with As2O3 and / or Sb2O3, i.e. in the absence of SnO2.

[0062] In one development of the invention, the glass ceramic comprises the following components in weight percent on an oxide basis: SiO262~67 Al2O319~23 Li2O 2.4~3.1 Na2O 0~1 K2O 0~1 MgO 0~1 CaO 0~1.2 BaO >2.5 ZnO >2.5 TiO2<3.0 ZrO2>1.5.

[0063] Furthermore, such glass-ceramics may also contain SrO, the SrO content of which mainly comes from impurities in the raw materials used to produce the glass-ceramics. In this case, SrO contributes, among other things, to the scattering of light by the glass-ceramics. It is therefore advantageous to keep the SrO content in the glass-ceramics as low as possible.

[0064] The following table contains three further developments of the composition in wt. % on an oxide basis of the glass-ceramics according to the invention: [Table 1]

[0065] In particular, the above composition may be free of K2O, except for unavoidable impurities.

[0066] In contrast to this, three alternative developments of the composition in wt. % on an oxide basis of the glass-ceramics according to the invention are given below: [Table 2]

[0067] Three further developments of the composition in wt. % on an oxide basis of the glass-ceramics according to the invention are given below: [Table 3]

[0068] In addition to the specifically named components of the above compositions, the corresponding glass-ceramics can also contain other components, in particular fining agents.

[0069] In this case, the fining of the green glasses according to the compositions mentioned above can be carried out using SnO2, using a combination of SnO2 with As2O3 and / or Sb2O3, or using As2O3 and / or Sb2O3 only, i.e. in the absence of SnO2, where the limits given above can be set for the contents of the respective components in the composition.

[0070] In a preferred embodiment of the present invention, the transparent lithium aluminum silicate glass ceramics furthermore have a crystallite size in the high quartz solid solution phase of less than 80 nm, preferably less than 70 nm, particularly preferably less than 60 nm, very particularly preferably less than 50 nm.In this case, the crystallite size has a direct effect on the optical properties of the glass ceramics.For example, if the crystallite size is too large, the light scattering in the glass ceramics increases, which appears as cloudiness of the glass ceramics.

[0071] In a further development of the invention, the ratio of Al2O3 to TiO2 is in the range from 7 to 12, preferably in the range from 8 to 11, particularly preferably in the range from 8.5 to 10.5. It has been found that a ratio of Al2O3 to TiO2 in this range has a particularly advantageous effect on the saturation of the glass-ceramics while at the same time allowing a particularly stable ceramization.

[0072] The glass ceramics according to the invention are used as cooktops, fireplace sight glasses, grill or roasting tops, covers for combustion elements of gas grills, oven sight glasses, in particular oven sight glasses of pyrolysis furnaces, kitchen or laboratory workbenches or table tops, covers for lighting devices, in fire protection glazing and as safety glass, optionally in laminated composites, as carrier plates or as linings for furnaces in thermal processes or as back covers for portable electronic devices.

[0073] The glass ceramics according to the invention can in particular be used as cooktops, which can in this case be provided with a decorative or functional coating on the top and / or bottom surface in whole or in part. Touch sensors for operating the cooktop can also be provided on the bottom surface. These can be, for example, capacitive sensors that are printed, glued or pressed on.

[0074] The present invention will now be further described with reference to the following examples.

[0075] The crystallizable green glass of the example was melted at 1680°C for 4 hours from industrial batch raw materials commonly used in the glass industry. This choice of raw materials allows to achieve both the economical raw materials and the low content of undesirable impurities. After melting the batch in a sintered silica glass crucible, the melt was poured into a Pt / Rh crucible with an inner silica glass crucible and homogenized by stirring at 1640°C for 60 minutes. After this homogenization, the glass was refined at 1680°C for 3.5 hours. It was then poured into a mold measuring approximately 120×120×30 mm. 3 Workpieces of different sizes were produced and cooled to room temperature in a cooling furnace at 30 K / h starting from 650-670 °C depending on the viscosity of the glass in order to relieve stress. The poured workpieces were divided into sizes required for testing and sizes required for ceramization.

[0076] Ceramization of the samples in the green glass state was carried out in a ceramization process having the following steps: a) heating from room temperature to 740°C within 25 minutes; b) holding the temperature at 740°C for 20 minutes; c) increasing the temperature from 740°C to 780°C within 6.5 minutes; d) increasing the temperature from 780°C to 825°C within 20 minutes; e) increasing the temperature from 825°C to 910°C within 8.5 minutes; f) holding the temperature at 910°C for 10 minutes; g) cooling to room temperature within 125 minutes.

[0077] This ceramization process should be considered as exemplary: by varying the temperatures and times of the individual steps or adding further steps, e.g. additional holding times, it is possible to fine-tune the properties of the glass-ceramics.

[0078] The ceramization can be carried out, for example, with the following parameters: a) Heat from room temperature to 680℃-760℃ within 3-60 minutes. b) The crystallizable green glass is subjected to a nucleation temperature range T a Heat up to 800℃ in 10 to 100 minutes. c) The glass containing the crystallization nuclei is heated to a temperature range of 810°C to 930°C, which is a temperature range with a high crystal growth rate, within 5 to 80 minutes. d) holding the temperature at 810-930°C for 2-60 minutes; e) Cool to room temperature within less than 150 minutes.

[0079] The following table contains the compositions and material properties of examples according to the invention.

[0080] Here, the coefficient of thermal expansion CTE was measured by a method substantially based on the 1998 edition of DIN ISO 7991.

[0081] To measure the upper limit of devitrification temperature (OEG), the green glass was melted in a Pt / Rh10 crucible. The crucible was then held at various temperatures within the processing temperature range for 5 hours. The highest temperature at which the first crystals appear at the interface between the glass melt and the crucible wall determines the OEG.

[0082] The working point (T4) of the green glass was determined according to DIN ISO 7884-2 using a stirring viscometer.

[0083] When the green glass transforms into a glass-ceramic, the density increases because the crystalline phase is denser than the amorphous glass. The so-called shrinkage ratio describes the linear change in length when the green glass transforms into a glass-ceramic. The shrinkage ratio in percent is calculated from the density of the green glass and the density of the glass-ceramic as follows:

number

[0084] T g denotes the transformation temperature of the green glass, also known as the glass transition temperature, which is measured by dilatometry.

[0085] Light transmittance τ vis is measured in the wavelength range 380-780 nm using standard illuminant D65 and a 2° observer in accordance with the specifications of DIN 5033. This value corresponds to the luminance Y in the CIExyY color space. This value is a measure of the luminance perception of the human eye.

[0086] The transmission spectra were measured according to ISO 15368:2021. Table 2 lists examples of the spectral transmittance “T@···” at wavelengths of 470 nm, 600 nm, 630 nm, 700 nm, 950 nm, and 1600 nm.

[0087] The color coordinates in the CIExyY and CIELab color spaces were determined according to the CIE 1932 specifications using a 2° observer and transmitted light of standard illuminant D65.

[0088] All transmittance measurements were performed on 4 mm thick samples that were smooth on both sides.

[0089] The "HQMK phase content" which is the volume fraction and the "HQMK crystallite size" which is the crystallite size of the crystalline phase were determined from the X-ray diffraction spectrum by Rietveld analysis.

[0090] [Table 4-1] [Table 4-2]

[0091] [Table 5-1] [Table 5-2] [Table 5-3]

Claims

1. A transparent lithium aluminum silicate glass-ceramic, A thermal expansion coefficient in the range of 20°C to 700°C is -0.8 to 1.5 ppm / K; Light transmittance τ at a thickness of 4 mm vis exceeds 75%, and the saturation C at a thickness of 4 mm * is less than 10, The following, in weight percent on an oxide basis: Yes 2 62~68 <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> 1124 Li 2 O 2.4~3.1 BaO >2.5 ZnO > 2.5 ZrO 2 >1.5 Na 2 O 0~1 K 2 O 0~1 A transparent lithium aluminum silicate glass-ceramic having a composition comprising:

2. The glass ceramic contains Cr except for unavoidable impurities. 2 O 3 , V 2 O 5 , MnO 2 and MoO 3 2. The transparent lithium aluminum silicate glass ceramic of claim 1, which is free of

3. The transparent lithium aluminum silicate glass ceramics preferably contain less than 3.0% by weight, more preferably less than 2.7% by weight, particularly preferably less than 2.5% by weight, very particularly preferably less than 2.4% by weight of TiO 2 3. The transparent lithium aluminum silicate glass ceramic according to claim 1, comprising:

4. The transparent lithium aluminum silicate glass ceramics preferably contain less than 0.05% by weight, more preferably less than 0.04% by weight, particularly preferably less than 0.03% by weight, very particularly preferably less than 0.02% by weight of Fe. 2 O 3 4. The transparent lithium aluminum silicate glass ceramic according to claim 1, further comprising:

5. 5. The transparent lithium aluminum silicate glass ceramic according to claim 1 , wherein the transparent lithium aluminum silicate glass ceramic comprises less than 1.2% by weight, preferably less than 1.0% by weight, particularly preferably less than 0.8% by weight, very particularly preferably less than 0.5% by weight of MgO.

6. 6. The transparent lithium aluminum silicate glass ceramic according to claim 1 , characterized in that it contains less than 1.2% by weight, preferably less than 1.0% by weight, particularly preferably less than 0.8% by weight and very particularly preferably less than 0.5% by weight of CaO.

7. The transparent lithium aluminum silicate glass ceramics preferably contain less than 0.2% by weight, more preferably less than 0.15% by weight, and particularly preferably less than 0.1% by weight, of SnO. 2 7. The transparent lithium aluminum silicate glass ceramic according to claim 1, comprising:

8. The transparent lithium aluminum silicate glass ceramic contains SnO except for unavoidable impurities. 2 and 0.5% to 1.5% by weight of As 2 O 3 and / or Sb 2 O 3 8. The transparent lithium aluminum silicate glass ceramic according to claim 1, comprising:

9. The transparent lithium aluminum silicate glass ceramic contains 0.01 to 0.07 wt. % Nd 2 O 3 9. The transparent lithium aluminum silicate glass ceramic according to claim 1, characterized in that it comprises

10. 20. The transparent lithium aluminum silicate glass-ceramic, comprising, in weight percent on an oxide basis: Yes 2 62~67 <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> 11~23 Li 2 O 2.4~3.1 Na 2 O 0~1 K 2 O 0~1 MgO 0-1 CaO 0-1.2 BaO >2.5 ZnO > 2.5 TO 2 <3.0 ZrO 2 >1.5 9. The transparent lithium aluminum silicate glass ceramic according to claim 7 or 8, characterized in that it comprises

11. 11. The transparent lithium aluminum silicate glass ceramic according to claim 1, characterized in that the transparent lithium aluminum silicate glass ceramic has a crystallite size in the high quartz solid solution phase of less than 80 nm.

12. TiO 2 Al 2 O 3 12. The transparent lithium aluminum silicate glass ceramic according to claim 1, wherein the ratio is in the range from 7 to 12, preferably in the range from 8 to 11, particularly preferably in the range from 8.5 to 10.

5.

13. 13. Use of the glass ceramics according to any one of claims 1 to 12 as cooktops, fireplace sight glasses, grill or roasting tops, covers for combustion elements of gas grills, oven sight glasses, in particular oven sight glasses of pyrolysis furnaces, kitchen or laboratory workbenches or table tops, covers for lighting devices, in fire protection glazing and as safety glass, optionally in laminated composites, as carrier plates or as linings for furnaces in thermal processes or as back covers for portable electronic devices.